Effect of Flaming Period on the Rejection Power of Plantain (Musa Sapientum L.) in Situ at Gbadolite in the Democratic Republic of Congo - Molongo Mokondande Médard; Litucha Bakokola Joseph; Okungo Lotokola Albert; Songbo Kwedugbu Médard; Monde te-Kazangba Gofroid (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The present study was carried out to observe the effect of buckling periods on the rejection power of plantain (Musa sapientum L.) in situ at Gbadolite in the Democratic Republic of Congo. The experimental set-up chosen was that of randomized complete blocks comprising 4 blocks and 4 treatments arranged in single rows; the subjects were planted at distances of 3 m x 3 m. The treatments were as follows: T0: Untreated or non-flambé subject; T1: Flambé subject at 2 months from planting; T2: Flambé subject at 4 months and T3: Flambé subject at 6 months from planting. Each plot consisted of 10 plants. Flambéing was carried out according to the flambé period, by mowing and assembling the dry phytomasses around the test plants, and finally, incineration by running fire or moderate heat, "flambage" during the cool moment to avoid plant death due to temperature rise. It was observed that the temperature varied between 27.17°C and 28.95°C before flaming and between 72.50°C and 73.25°C during flaming. An average of 6 shoots per bulb were counted for the controls, and 15, 18 and 23 shoots for the flamed corms at 2, 4 and 6 months of planting, respectively, under in situ conditions. In this study, the flaming process, in relation to the period of its application, increased the rejection rate to 150%, 200% and 283.33% respectively for subjects flamed at 2, 4 and 6 months. Examination of all the parameters studied reveals that the agro-ecological zone of Gbadolite in the Democratic Republic of Congo, with uni-modal rainfall, clayey-sandy soil, with the flaming technique constitutes in combination with the period of application one of the factors activating the rejection power of plantain.